Frihed til kaerlighed hos Luther og Kierkegaard - Welz, Claudia (Dansk teologisk tidsskrift, 2009)
Resumé ”You shall love thy neighbour as yourself”. How does commanded love turn into the praxis of loving? According to Kierkegaard, works of love are not just grounded in human agency and capability, but are done in the Spirit of love. The key words of Kierkegaard’s explanation – ‘spirit’, ‘interiority’, ‘gift’ and ‘debt’ – are decisive also for the Pauline-Lutheran tradition. This tradition holds that the human being becomes free to love his neighbor only if he has been freed from self-centredness. Yet, what does that imply for the view of the person, who is simul iustus et peccator, at once a sinner and justified, at once ‘the old Adam’ and ‘a new creature’? The anthropological implications are controversial, especially in regard to the relation between the ‘inner’ and the ‘outer’, the ‘old’ and the ‘new’ person, the sinner’s nature and his self-transcendence. Kierkegaard’s insights could contribute to the clarification, if not correction, of some notorious problems that belong to Luther’s heritage.